The value of coastal lagoons: Case study of recreation at the Ria de Aveiro, Portugal in comparison to the Coorong, Australia - Clara, Inês (2020)
Coastal lagoons are some of the most inhabited and yet threatened ecosystems in the world. Cultural services in coastal lagoons are important for supporting human wellbeing and therefore their valuation is gaining recognition among decision makers responsible for managing development that affects these areas. This study is focused on the recreational aspect of cultural services employing two econometric methods revealed and stated preference – to estimate the non-market value of recreation at two coastal lagoons. This is part of an international and interdisciplinary study conducted by ecologists and economists. The same survey questionnaire, with minor adaptations, employing the same valuation methods, i.e. Travel Cost Method (TCM) and Contingent Valuation Method (CVM), were used at both the Coorong (Australia) and the Ria de Aveiro (Portugal). Results of the two surveys at the two sites revealed largely similar visitor profiles. The estimated values of Consumer Surplus obtained were 132€ and 160€ (per adult and per day) according to the TCM for the Australian and the Portuguese lagoons respectively, and 103€ and 110€, respectively with the CVM. These quantitative monetary estimates of non-market recreational visitor values represent part of the total value of these coastal lagoons and can be used directly as input for evaluations of alternative management options using Cost-Benefit Analysis. As such, the estimates fill part of what has previously been an information gap that has prevented a full accounting of the net benefit of alternative options. Now, with a more complete set of values, managers can better assess the extent to which financial resources should be allocated towards nature conservation vis à vis development.